COPD in Germany: Use of Diagnostic Measures Including Blood Eosinophil Counts in Daily Practice - Greulich, T.; Töpfer, V.; Hennig, M.; Orehounig, C. C.; Ams, K.; Mohrlang, C. D.; Killian, P. H.; Kardos, P. (Pneumologie, 2020)
Background Accumulating evidence on the role of blood eosinophils as a biomarker prompted the Global Initiative for Chronic Obstructive Lung Disease (GOLD) committee to refine the existing treatment algorithm by incorporating eosinophil counts into treatment recommendations. However, there is a lack of data on when, why and how frequently such blood tests and other measures are being performed by German private respiratory specialists.Methods A questionnaire evaluating doctors’ opinions on the use of diagnostic measures at initial diagnosis and during follow-up, including blood eosinophil count in patients with COPD, was completed by 27 respiratory specialists. Medical records from the past 12 months of 251 patients treated by the same physicians were reviewed retrospectively to investigate the use of these measures.Results Body plethysmography (100 % of doctors) and chest X-ray (96.3 %) were the most commonly used measures according to the doctor’s questionnaire; other measures were COPD assessment test (CAT; 85.2 %) and blood eosinophil count (81.5 %). The evaluation of patients’ medical records revealed that body plethysmography was performed in 72.7 %, the CAT in 61.8 % and chest X-ray in 40.6 % of patients. Blood eosinophil count was measured in 7.2 %.Conclusions In line with the GOLD recommendations, these results confirm that lung function, imaging and patient-reported outcome questionnaires play a crucial role in managing COPD. Our analyses reveal that measurement of the blood eosinophil count gained importance due to physicians’ increased awareness of these cells as a useful biomarker. However, this test seems to be performed mainly for initial diagnosis and not on a regular basis.